PENINGKATAN KINERJA KARYAWAN BERBASIS KECERDASAN EMOSIONAL DAN LINGKUNGAN KERJA - Nailin Nikmatul Maulidiyah; Ardini Manzilatun Nikmah (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2022)
This study aims to determine the effect of emotional intelligence and work environment on employee performance. This study is a qualitative research which is sourced from the existing theories and relevant empirical research journals. The results of this study showed that emotional intelligence and work environment has a positive effect on employee performance. Keywords: Emotional Intelligence ; Work Environment ; Performance